Historical ethnopharmacology of the herbalists from Krummhübel in the Sudety Mountains (seventeenth to nineteenth century), Silesia - Krzysztof Spałek; Izabela Spielvogel; Małgorzata Proćków; Jarosław Proćków (BMC, 2019)
Abstract Background Krummhübel (after 1945, Karpacz) in the Sudety Mountains (now SW Poland) was called "the village of pharmacists". At the end of the seventeenth century, there were 57 households, of which about 40 were inhabited by herbalists. Krummhübel herbalists were the first in the Sudety region who applied medicinal mixtures for the treatment of various diseases (using, among others, plants, oils, minerals and even viper venom) in contrast to previous herbalists who only indicated the use of individual plant species for specific diseases. Riesengebirge (in Polish Karkonosze) potions were sold in Austria, the Czech Republic, Poland and Russia, and some of them could even be purchased in Scandinavia and England. The purpose of this paper is an ethnopharmacological analysis of historical texts of herbalists from Krummhübel. Based on their recipes, we analysed the use reports of drugs. Recently, research on ethnobotany and ethnopharmacological analyses of historical materials or egodocuments related to formulations used in folk medicine have become an important source of acquiring knowledge about new medicines. Methods Based on 46 recipes of Krummhübel herbalists re-written by Reitzig (1943), we analysed the use reports of drugs which included plant taxa and other constituents such as animal formulations, fungi, inorganic and organic substances and minerals as well as tinctures (with alcohol/spirit) and elixirs (without alcohol/spirit). For each usage mentioned in the text, we recorded (i) the putative botanical identity of the taxon; (ii) the plant family or origin of other than the plant constituent; (iii) the reported plant part; (iv) the number of the recipe; (v) the name of the recipe; (vi) the vernacular name of ingredient; (vii) the described symptom, ailment or specific use; (viii) our modern (viz. biomedical) interpretation of the described symptom or ailment; (ix) the mode of administration; and (x) the category of use under which we filed the specific use. We also cross-checked the medicinal plants of Krummhübel herbalists with the species described in old manuscripts and regional surveys and compared their use with contemporary plant use. Results The paper introduces the generated database comprising 348 use reports of 46 drugs based on 70 plant taxa and other constituents. Besides, we address patterns such as the frequent recommendation of Fabaceae herbs for respiratory system issue and gynaecology and Asteraceae for respiratory system and cardiovascular problems. Gastrointestinal use reports are based on Asphodelaceae, Burseraceae and Rosaceae species. Conclusions Remedies that lost importance over time as well as drugs used for diseases now controlled by conventional medicine may be interesting starting points for research on herbal medicine and drug discovery. It seems to be important to attempt to reproduce therapeutic mixtures from the preserved recipes of Krummhübel herbalists, which offers an opportunity to learn more about the real effects of the former medicines and their therapeutic activity. The obtained data can also be used to search for new drugs.